MANFAAT OLAHRAGA RINGAN JALAN KAKI PADA REMAJA, IBU HAMIL DAN LANSIA: LITERATURE REVIEW - Andi Atssam Mappanyukki; Yadi Jayadilaga (Pustaka Katulistiwa : Karya Tulis Ilmiah Keperawatan, 2024)
This study aims to identify the benefits of light exercise, specifically walking, for adolescents, pregnant women, and the elderly through a literature review. Data were collected from various sources such as Google Scholar, ScienceDirect, and Pubmed using keywords in Indonesian and English. The review findings indicate that walking provides various benefits for each group. For adolescents, benefits include a reduction in body mass index, obesity management, and alleviation of menstrual pain. For pregnant women, benefits encompass improved sleep quality, reduced risk of hypertension, and enhanced mood. For the elderly, benefits include lowered blood pressure, reduced risk of dementia, and improved balance.